The Impact of Critically Reflective Teaching: A Continuum of Rhetoric. (2nd April 2016) - Burbank, Mary D.; Ramirez, Laurie A.; Bates, Alisa J.
ABSTRACT: This qualitative case study explored teaching approaches designed to develop critically reflective thinking (CRT) for preservice teachers in an urban, secondary teacher preparation program. Despite concerted use of CRT within course lessons, online discussions, and case studies, participants demonstrated varying degrees in their understanding of diversity and how they will respond in their teaching practices. Findings speak to the critical importance for teacher preparation that acknowledges conceptual readiness and receptivity among preservice teachers when challenging beliefs regarding diversity using critically reflective pedagogy. Findings will inform other teacher educators in the development of pedagogy and the tools for supporting critically reflective thinking, problem solving, and decision making in urban schools.